Analisis Validasi dan Kepraktisan Pengembangan Media Pembelajaran Papan Pecahan pada Siswa Kelas 2 Sekolah Dasar Kecamatan Semen: Analysis of Validation and Practicality of Fraction Board Learning Media Development for Grade 2 Elementary School Students in Semen District - Ambaria, Ambaria; Nurmilawati, Mumun; Zunaidah, Farida Nurlaila (Efektor, 2023)
Learning media is really needed in the learning process, especially for elementary school students, because media will make it easier to understand concepts, especially mathematics subjects. This research aims to determine the validation criteria and practicality of developing fraction board learning media for grade 2 elementary school students in Semen District. The research method used is descriptive research method. The data analysis technique used is quantitative qualitative. Based on the results of the data obtained, according to media experts, it shows that the level of validation for the development of fraction board learning media for grade 2 elementary school students in Semen District is included in the very valid criteria with information that is very good for use with a percentage of 87.27%, while according to material experts it shows that the level of validation for the development of fraction board learning materials for grade 2 elementary school students in Semen District is included in the very valid criteria with information that is very good for use with a percentage of 100%. Meanwhile, the teacher response questionnaire got a score of 87%, while the student response questionnaire got a score of 92.85%, which shows that the fraction board learning media is very practical and can be used without revision.